2022
DOI: 10.3389/fmats.2022.833593
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Asphalt Modified by Packaging Waste EVA and Graphene Oxide

Abstract: A composite modifier made from waste ethylene-vinyl acetate copolymer (WEVA) and graphene oxide (GO) is used to modify asphalt used to pave the roadway. At the same time, the effect of GO on the related properties of modified composite asphalt is investigated in terms of softening point, penetration, ductility, as well as distribution. The preparation of the composite modifier can reduce the modification’s complexity and enhance the modifier’s dispersion in the asphalt system in the storage phase. By increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Consequently, green fluorescent spots with various sizes are observed in Figure b, indicating a relatively dense distribution of DG in asphalt. In comparison to Figure a, DG powders are evenly dispersed in asphalt, as illustrated in Figure b, thereby enhancing the overall performance of modified asphalt …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, green fluorescent spots with various sizes are observed in Figure b, indicating a relatively dense distribution of DG in asphalt. In comparison to Figure a, DG powders are evenly dispersed in asphalt, as illustrated in Figure b, thereby enhancing the overall performance of modified asphalt …”
Section: Resultsmentioning
confidence: 98%
“…In comparison to Figure 4a, DG powders are evenly dispersed in asphalt, as illustrated in Figure 4b, thereby enhancing the overall performance of modified asphalt. 29 Chemical Composition Changes of Asphalt after Adding DG. To discuss the impacts of added DG on the chemical compositions or functional groups of asphalt, FTIR tests are performed, and Figure 5 provides test results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthetic polymers, on the other hand, are mostly developed via chemical reactions involving various polymerization processes. A recent investigation has shown that not all polymers are suitable for bitumen modification; however, polymer-modified bitumen has been reported to show reduced thermal sensitivity, enhanced resistance to cracking, rutting, fatigue, and moisture [ [115] , [116] , [117] ]. Polymeric modification of bitumen has received significant attention and several researchers have studied various polymer modification techniques to address severe rutting and cracking challenges in road pavements [ [118] , [119] , [120] ].…”
Section: Polymers and Polymeric Bitumenmentioning
confidence: 99%
“…In the same vein, grafting certain additives with waste polymer materials can improve the dispersion and enhance their properties. Zhang et al [ 117 , 181 ] investigated the effects of self-prepared graphene oxide (GO) emulsion on the dispersion of WEVA in bitumen. The GO incorporated in 0.08 % amount was able to reduce WEVA particle aggregation in the modified asphalt system.…”
Section: Sustainable Pavementsmentioning
confidence: 99%
“…Due to its high potential energy barrier, a variety of gases (such as He, O2, CO2, etc.) will be shielded by GO, which can inhibit the aging and crack resistance of polymers, and is very suitable for the modification of typical viscoelastic polymer compounds such as asphalt [9,10]. In addition, the surface of GO contains many polar oxygen-containing groups, such as a carboxyl group, hydroxyl group, epoxy group, and an ester group, which makes it have highly active sites and easy to be compounded by the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%